2000
DOI: 10.1139/gen-43-3-512
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA in peach (<i>Prunus persica</i> L. Batsch) and its use in fingerprinting and testing the genetic origin of cultivars

Abstract: We isolated and sequenced 26 microsatellites from two genomic libraries of peach cultivar 'Redhaven', enriched for AC/GT and AG/CT repeats, respectively. For 17 of these microsatellites, it was possible to demonstrate Mendelian inheritance. Microsatellite polymorphism was assayed in 50 peach and nectarine cultivars. Of the 1300 PCRs carried out, all but two produced amplified products of the expected size. All microsatellites were polymorphic, showing 2-8 alleles per locus. Heterozygosity ranged from 0.04-0.74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(88 citation statements)
references
References 0 publications
9
75
3
1
Order By: Relevance
“…These results agreed with the findings of Wang et al (2002) who found that most SSRs are not specifically linked to gene loci of immediate interest and developing an SSR map is very time consuming and expensive. Either these results were in agreement with Testolin et al (2000) who gave some examples to the utility of SSRs for pedigree determination of several peach cultivars. Aranzana et al, (2003) reported that the available SSRs on the Prunus saturated map allowing them to develop a resource useful for map comparison or MAS in fruit crops.…”
Section: Ssrs Molecular Markerssupporting
confidence: 89%
See 1 more Smart Citation
“…These results agreed with the findings of Wang et al (2002) who found that most SSRs are not specifically linked to gene loci of immediate interest and developing an SSR map is very time consuming and expensive. Either these results were in agreement with Testolin et al (2000) who gave some examples to the utility of SSRs for pedigree determination of several peach cultivars. Aranzana et al, (2003) reported that the available SSRs on the Prunus saturated map allowing them to develop a resource useful for map comparison or MAS in fruit crops.…”
Section: Ssrs Molecular Markerssupporting
confidence: 89%
“…Microsatellite or Simple Sequence Repeats (SSRs) are the best available choice of markers for peach genetics and breeding, they are generally codominant, highly polymorphic, and can be found in large numbers covering the whole genome of any species (Sosinski et al, 2000). Many SSRs have been developed in peach (Testolin et al, 2000;Aranzana et al, 2002;Dirlewanger et al, 2002). The objectives of this study were to:…”
Section: Fruit Breedingmentioning
confidence: 99%
“…The DNA was quantified on a NanoDrop system (Thermo Fisher Scientific, Schwerte, Germany) and diluted to a standardized DNA concentration of 10 ng ml À1 . We amplified eight microsatellite loci (Testolin et al, 2000;Dirlewanger et al, 2002;Schueler et al, 2003), using the combinations and conditions described in , with the only difference being the labelling from primers UDP98_411 (FAM), UDP98_412 (FAM) and BPPCT_040 (HEX). Fragments were analysed on a Megabace genetic analyser (Amersham Biosciences, Buckinghamshire, UK) using the Megabace ET 400-R size standard (GE Healthcare, Munich, Germany).…”
Section: Genetic Analysismentioning
confidence: 99%
“…This method could certainly visualize the variations of both two S-alleles, which respective individuals possess, implying that null alleles are unlikely to be detected at the S-locus. Genotypes at 11 nuclear SSR loci, BPPCT005, 014, 026, 028, 034, 037, 038 and 040 (Dirlewanger et al, 2002), UDP96-001 (Cipriani et al, 1999), UDP98-412 (Testolin et al, 2000) and pchcms5 (Sosinski et al, 2000), were also scored using the method described by Kato et al (2011). Part of the genotypes had been already determined in our previous studies (Kato and Mukai, 2004;Kato et al, 2007Kato et al, , 2011.…”
Section: Genotyping Samples At the S-locus And Ssr Locimentioning
confidence: 99%